What limits Muslim communities' access to nature? Barriers and opportunities in the United Kingdom. (June 2023) - Edwards, Rachael C; Larson, Brendon MH; Burdsey, Daniel
Recreation in protected areas can greatly contribute to health and wellbeing, but there exist significant demographic disparities in protected area use across Europe and North America. Minority ethnic groups, in particular, are often underrepresented in protected areas due to a variety of cultural, economic, and discriminatory barriers. Muslims are one of the fastest growing minority ethnic communities in Western countries but have received little study in the context of protected areas. More research is therefore needed to understand protected area exclusion as experienced by Muslim communities. Through 14 in-depth interviews with Muslim community leaders in the United Kingdom, we explored the socio-cultural barriers and opportunities that contribute to the accessibility of protected areas for Muslims. As the majority of our participants were women, this study addresses the underrepresentation of diverse female voices in research on Muslims and leisure and foregrounds Muslim women as agents in their recreational lives. We found that a wide variety of factors can inhibit access, cumulatively resulting in several layers of exclusion. Primary barriers included a lack of inclusive imagery, insufficient facilities for social gathering, prior instances of discrimination, the perceived whiteness of protected areas, and unfamiliarity with these spaces. Several barriers related to the wilderness ideology that is embedded across many aspects of protected area marketing, design, and management as it does not embrace collectivist aspects of Muslim cultures. The level of "naturalness" associated with protected areas, however, did not emerge as a barrier. We also identified many opportunities, including the stewardship role of humans depicted within Islam. Lastly, we discuss the management implications for protected areas that emerge from our results. This research demonstrates that to foster a sense of belonging for Muslim communities, protected area managers must consider many socio-cultural dimensions of accessibility, holistically engage with Muslim communities, and embrace diverse worldviews relating to the human–nature relationship.